Do women advance equity? The effect of gender leadership composition on LGBT-friendly policies in American firms. (July 2016) - Cook, Alison; Glass, Christy
We advance the literature on the demographic factors that shape organizational outcomes by analyzing the impact of the gender composition of firm leadership on the likelihood that a firm will adopt lesbian, gay, bisexual and transgender (LGBT)-friendly policies. Drawing on social role and token theory, we test the relative impact of CEO gender and the gender composition of the board of directors separately and together in order to identify the effects of gender diversity at the top of the organization. We rely on a unique data set that includes corporate policies (gender identity and sexual orientation non-discrimination policies, domestic-partner benefits, and overall corporate equality index scores) as well as the gender of the CEO and board of directors among Fortune 500 firms over a 10-year period. Our findings suggest that firms with gender-diverse boards are more likely than other firms to offer LGBT-friendly policies, whereas findings for firms with women CEOs offer mixed results.